DESIGNING BOOKS WHICH ARE COMMUNICATION TOOLS AS GRAPHIC PRODUCTS AND THE IMPORTANCE OF THE DESIGN IN POETRY BOOKS - Kavuran, Tamer (Anadolu Univ, 2016)
In this study the necessity of designing books which have an important role in the progress of our civilization has been discussed. 'Book' has been defined, it has been laid emphasis on its development process and significance; besides, book genres have been interpreted and knowledge has been given about the poetry book and poetry as well. 'Book design' has also been taken into account in general while the importance of design in poetry books, its reasons and the remarkable factors in the process of designing are being emphasized. In this survey design problems of the book-concurrently a graphic product-have been examined regarding co-occurrence of writer/poet-publisher-designer. In the survey it has been tried to be described through the index including the list of scientific publications and scanning of the cores. In accordance with the findings obtained from the scientific data it has been made suggestions, concluding that visual, aesthetic, functional and technical concerns are necessary in designing the book as a graphic product.
Keywords: Book Design; Graphic Design; Poetry Book; Publisher